From Play to Proficiency: Using English Podcasts to Sharpen Listening Skills - Riska Hazmatul Askia; Aminah Aminah; Maf'ulah Maf'ulah; Anjar Kusuma Dewi (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study examines the effectiveness of English podcasts as a medium for improving the listening comprehension of eighth-grade students at SMP Negeri 1 Banawa Tengah. Motivated by students’ low listening proficiency and limited exposure to authentic English audio, this research applied a quantitative quasi-experimental design with two groups: an experimental class that received podcast-based instruction over six sessions, and a control class that did not use podcasts. Data were collected through pre-tests and post-tests to measure listening gains. The results showed that the experimental group’s mean post-test score increased from 37 to 52, with nine students meeting the minimum passing standard, while the control group’s scores remained largely unchanged. A t-test revealed a significant difference (t = 7.39 > t-table = 2.009, p < 0.05). These findings demonstrate that integrating podcasts into English instruction can significantly enhance students’ listening comprehension.